The method of domain model creation using frames in the development of monitoring systems - Sopel, М.F.; Velev, D.D.; Furtat, Yu.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2013)
The paper describes an approach to the problem of creating a domain model, and a parametric model of controlled engineering objects. The approach is based on using set theory and the concepts of frames, explained all the necessary concepts and attributes of the models are explained, and an option is offered of a computer (machine) implementation.